A visual tool for analysing teacher and student interactions in a design studio setting. Issue 1 (2nd April 2016) - Ferreira, João; Christiaans, Henri; Almendra, Rita
Abstract: Teacher and student interaction in a design studio setting has always been the basis of design education. A fundamental difficulty of design education is that the content of these one-on-one meetings between teacher and students remains remarkably implicit. In this paper, we present an explorative study that uses the design grammar model (DGM) as an observational framework for teacher–student interactions. The DGM is rooted on the concept of design grammar that can be broadly defined as the visual language used to design. The study focuses on the industrial design junior students' meetings with their teacher; our research proceeds from a protocol analysis of the transcripts that are coded according to the DGM. The resulting data are then used to develop a series of diagrams that are employed as a visual analysis tool. The diagrams synthesise and convey large amounts of data that permit immediate analysis and elicit new interpretations. The study resulted in encouraging results regarding the DGM's potential as an analysis tool for teacher and student interactions, as well as a diagnostic tool for teachers.